Molecular Targets and Signaling Pathways of microRNA-122 in Hepatocellular Carcinoma - Kwang-Hoon Chun (Pharmaceutics, 2022)
Hepatocellular carcinoma (HCC) is one of the leading global causes of cancer mortality. MicroRNAs (miRNAs) are small interfering RNAs that alleviate the levels of protein expression by suppressing translation, inducing mRNA cleavage, and promoting mRNA degradation. miR-122 is the most abundant miRNA in the liver and is responsible for several liver-specific functions, including metabolism, cellular growth and differentiation, and hepatitis virus replication. Recent studies have shown that aberrant regulation of miR-122 is a key factor contributing to the development of HCC. In this review, the signaling pathways and the molecular targets of miR-122 involved in the progression of HCC have been summarized, and the importance of miR-122 in therapy has been discussed.